Public Libraries and Science Awareness - Majumdar, Suchismita; Banerjee, Swapna (Journal of Information and Knowledge, 2008)
Science Awareness is vital for every individual in a society and every category of people in a community. Public Library has ample scope, multidimentional modes and approaches, aids and tools at its end to ensure science awareness. It plays a leading role in taking up various sociological issues at all strata of society and community. The nature and extent of science awareness varies from an urban to a rural one, moulding its services accordingly. Technological advancement and IT mobilization provides wider perspective, giving a thrust towards fulfillment of its goal. However, lacunae still exist which needs to be traced out and possible efforts are to be applied for making the public libraries a pivotal centre in the science awareness programme of a country.